Association between traffic-related air pollution and hospital readmissions for rheumatoid arthritis in Hefei, China: A time-series study. (1st January 2021) - Wu, Qian; Xu, Zhiwei; Dan, Yi-Lin; Cheng, Jian; Zhao, Chan-Na; Mao, Yan-Mei; Xiang, Kun; Hu, Yu-Qian; He, Yi-Sheng; Pan, Hai-Feng
Abstract: Air pollution is an important risk factor for autoimmune diseases, but its association with the recurrence of rheumatoid arthritis (RA) remains unclear so far. This study aimed to investigate the short-term association between traffic-related air pollutants and hospital readmissions for RA in Hefei, China. Data on daily hospital readmissions for RA and traffic-related air pollutants, including particulate matter (PM2.5 and PM10 ), nitrogen dioxide (NO2 ), and carbon monoxide (CO), from 2014 to 2018 were retrieved. A time-series approach using generalized linear regression model was employed. The analysis was further stratified by sex, age and season. A total of 1153 readmissions for RA were reported during the study period. A significant association between high-concentration PM2.5 (90th percentile) and RA readmissions was observed on lag1 (relative risk (RR) = 1.09, 95% confidence interval (CI): 1.01–1.19) and lasted until lag3 (RR = 1.06, 95%CI: 1.01–1.12). From lag2 to lag5, high-concentration NO2 (90th percentile) was associated with increased risk of RA readmissions, with the highest RR observed at lag 4 (1.11, 95%CI: 1.05–1.17). Stratified analyses indicated that females and the elderly appeared to be more vulnerable to high-concentration PM2.5 and NO2 exposure. High-concentration PM2.5 and NO2 in cold seasons were consistently significantly associated with increased risk of RA readmissions. Exposure to high-concentration PM2.5 and NO2 was associated with increased risk of RA readmissions. Protective measures against the exposure to high-concentration PM2.5 and NO2 should be taken to reduce the recurrence risk in RA patients, especially in females, the elderly and during cold seasons. Graphical abstract: Image 1 Highlights: This is the first study on the association between traffic-related air pollution and RA. Females and the elderly were more vulnerable to high particulate matter (PM2.5 ). Females and the elderly were more susceptible to high nitrogen dioxide (NO2 ). The associations of high PM2.5 and NO2 with RA were both pronounced in cold seasons. Abstract : Capsule: Association between traffic-related air pollutants and increased risk of RA readmissions.